Mutations in the NSD1 gene in patients with Sotos syndrome associate with endocrine and paracrine alterations in the IGF system - De Boer, L; Van Duyvenvoorde, HA; Willemstein-Van Hove, EC; Hoogerbrugge, CM; Van Doorn, J; Maassen, JA; Karperien, M; Wit, JM (European journal of endocrinology, 2004)
OBJECTIVE: To investigate the effect of nuclear receptor Su-var, 3-9, enhancer of zeste, trithorax (SET) domain-containing protein 1 (NSD1) gene alteration in patients with Sotos syndrome on plasma IGFs and IGF-binding proteins (IGFBPs), as well as on the IGF/IGFBP system activity at the tissue level. DESIGN: Twenty-nine patients suspected of Sotos syndrome were divided into two groups: patients with heterozygous deletions or mutations in the NSD1 gene (NSD1(+/-)) (n=11) and subjects without (NSD1(+/+)) (n=18). Plasma samples (n=29) and skin fibroblasts (n=23) were obtained. The results of both groups were compared and related to reference values. METHODS: IGF-I, IGF-II, IGFBP-2, IGFBP-3, IGFBP-4 and IGFBP-6 levels were determined by RIAs. The mitogenic response of fibroblasts to IGFs was investigated by [methyl-(3)H]thymidine incorporation. IGFBP-3 levels in the culture media were measured by RIA. IGFBP-3 mRNA expression was determined by real time RT-PCR. RESULTS: NSD1(+/-) patients showed significantly altered levels of IGF-I (mean-1.2 SDS), IGF-II (-1.2), IGFBP-3 (-1.7), IGFBP-4 (-0.4), IGFBP-2 (+0.8) and IGFBP-6 (+1.5). The NSD1(+/+) patients did not differ from the reference, with the exception of the mean IGFBP-3 level (-1.3). Basal proliferation and mitogenic response to IGFs was diminished in NSD1(+/-) fibroblasts compared with NSD1(+/+) (basal, P=0.02; IGF-I, P<0.001; IGF-II, P=0.02). Compared with control fibroblasts, only the mitogenic response was diminished (basal, P=0.07; IGF-I, P=0.04; IGF-II, P=0.04). A trend of higher IGFBP-3 secretion after IGF-I stimulation (P=0.09) and 3.5-5 times higher mRNA expression of IGFBP-3 in basal conditions was found in NSD1(+/-) fibroblasts in comparison to controls. CONCLUSIONS: NSD1(+/-) patients show endocrine and paracrine changes in the IGF system. These changes may contribute to the abnormal growth pattern.